Exploring Narrative Structure and Immersion in the Game OMORI: Unpredictability and Trauma as Guiding Principles - Deanya Parahita Nauraputri Dewanto; Setefanus Suprajitno (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
This study analyzes the narrative structure of OMORI, a 2020 psychological horror RPG by Omocat, focusing on its portrayal of trauma through the protagonist Sunny. Incorporating Bal’s (2017) narratology and Wei’s (2011) narrative framework, this study examines techniques that contribute to unpredictability and trauma-driven narrative. Using Bermejo-Berros et al.’s (2022) narrative tension theory and Green and Brock’s (2000) transportation theory, the study reveals how each technique, respectively, incites immersive horror and emotional connection in players. Unpredictability can create immersive horror through narrative tension, whereas trauma-driven narrative may create an emotional connection by making the players sympathize with the character. Through its placement and presentation of sequences, the game evokes cognitive and emotional responses in players. The narrative structure in OMORI highlights the impact of unpredictability and trauma-driven narratives in game storytelling. Analyzing the game’s sequences and mechanics reveals their role in creating profound emotional experiences for players.